Locke’s Composition Principle and the Argument for God’s Immateriality - Tyler Hanck (Journal of Modern Philosophy)
Locke’s argument for God’s immateriality in Essay IV x is usually interpreted as involving a principle that in some way prohibits the causation of thought by matter. I reject these causal readings in favor of one that involves a principle which says a thinking being cannot be composed out of unthinking parts. This Composition Principle, as I call it, is crucial to understanding how Locke’s theistic argument can succeed in the face of his skepticism about the substance of matter and the cause of thought, as well as his belief in the possibility of thinking matter. It also explains why Locke held the soul’s immateriality to be highly probable.